A review of the court of appeal’s decision in Chief of naval staff Abuja & ors V. Eyo Archibong & Anor: the imperative ofexpanding the frontiers of fundamental rights enforcement law (2020)
This article examines whether joint application can be instituted by more than one persons in the enforcement of fundamental rights cases in Nigerian courts. It adopts the case study approach by reviewing five major Court of Appeal decisions on this subject. While majority of these decisions answered this question in the negative, few of the cases held the question in the affirmative, thereby unsettling the position of the law on this point. The legal implication is that it does not make for certainty of the law, subsequent courts can pick and choose which of the decisions to follow. This paper argues that there is need to expand and expound the frontiers of fundamental rights enforcement procedure law in order to accommodate joint application in fundamental rights claims. Appellate courts should not set aside judgement of trial courts simply because the action was instituted by more than one applicant, as this would amount to sacrificing justice on the altar of technicalities. While this article enjoins the Court of Appeal to uphold joint fundamental rights application in subsequent cases, it also advocates that the Supreme Court should maintain a liberal disposition in settling this point of law whenever the opportunity rises.